THE INFLUENCE OF DISCIPLINE AND WORK MOTIVATION ON EMPLOYEE PERFORMANCE - Muhammad Gandung (International Journal Multidisciplinary Science, 2024)
This research aims to determine the influence of discipline and work motivation on employees of PT Sejahtera PrimaPersada, South Jakarta. The population in this study were all employees of PT Sejahtera PrimaPersada South Jakarta, while the sample of all employees of PT Sejahtera PrimaPersada South Jakarta was 56. The sampling technique is saturated. The analytical tool used in this research is multiple linear regression. The partial research results show that discipline has a significant effect on the performance of employees of PT Sejahtera PrimaPersada South Jakarta, while work motivation has no significant effect on employee performance. Simultaneously, discipline and work motivation significantly affect the employees performance of PT Sejahtera PrimaPersada South Jakarta.